PENGARUH MODEL COURSE REVIEW HORAY TERHADAP KEMAMPUAN PEMECAHAN MASALAH KELAS X SMA NEGERI 4 KOTA BENGKULU - Nopriza Rahmawati; Saleh Haji; Agus Susanta (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to determine the effect of the Course Review Horay Model on the Problem-Solving Ability of Class X Students of SMA Negeri 4 Bengkulu City. This type of research uses Quasi Experiments. Data collection is done through tests. Data analysis used the Ancova test. The research sample was students at SMA Negeri 4 Bengkulu City class X MIPA 2 and X MIPA 5. The results showed that: (1) There was an effect of the Course Review Horay learning model on the problem-solving abilities of students in class X SMA Negeri 4 Bengkulu City by 31%. (2) There was an influence of the Course Review Horay Model on the problem-solving abilities of class X students at SMA Negeri 4 Bengkulu City after controlling for the covariate of students' initial ability of 38.5%. (3) The problem-solving ability achievement of class X students at SMA Negeri 4 Bengkulu City was taught using Learning the Course Review Horay model is better than classes taught by conventional learning